Biological properties of TW01 cells expressing latent membrane protein-1 gene of EBV-derived from nasopharyngeal carcinoma cells at different stages of malignancy - Tan, E.L.; Sam, C.K. (Experimental Oncology, 2007)
Background and Aim: Epstein—Barr virus (EBV), a human gammaherpesvirus is intimately associated with nasopharyngeal carcinoma (NPC), with the incidence of the virus detected in malignant tissues being close to 100% in NPC endemic areas. The viral latent gene, latent membrane protein 1 (LMP1), has all the typical characteristics of an oncogene and extensive studies have shown beyond doubt its abilities in cellular transformation giving rise to malignant phenotypes. The present study compares the gene sequence and biological properties of LMP1 gene derived from two patients with different stages of NPC – one presented with dysplastic, pre-malignant lesion and the other with malignant lesion. Methods: The sequences of the LMP1 genes derived from pre-malignant (NORLMP1) and malignant (NPCLMP1) tissues were compared. NORLMP1 and NPCLMP1 were expressed in TW01 cells and their biological properties conferred were assessed in terms of in vitro invasion capability, ability to resist apoptosis and regulation of E-cadherin (CDH1) expression. Results: NORLMP1 and NPCLMP1, possessed numerous amino acid changes with respect to the wild-type B95.8 LMP1. Both LMP1 variants demonstrated distinct biological properties when expressed in TW01 cells. NORLMP1-expressing TW01 cells exhibited more aggressive phenotypes than the NPCLMP1-expressing counterpart in terms of invasive ability, resistance to stimuli-induces apoptosis and regulation of CDH1 expression. Conclusion: It could be inferred from the present study that LMP1 genes derived from two patients with different stages of NPC differed in their gene sequences that manifested in distinct biological properties. Обоснование и цель: вирус Эпштейна—Барр (ВЭБ), герпесвирус человека, ассоциирован с развитием рака носоглотки (РНГ): вирус выявляют в малигнизированной ткани практически в 100% случаев.  Ген, кодирующий латентный мембранный белок 1 (LMP , обладает типичными характеристиками онкогена; в ряде исследований продемонстрирована его способность вызывать трансформацию клеток и развитие злокачественного фенотипа. В данной работе проведено сравнение нуклеотидной последовательности генов LMP , выделенных из ткани РНГ двух больных (с дисплазией/предраком и РНГ ІІ стадии соответственно) и биологических свойств клеток, трансфецированных этими генами. Методы: сравнивали нуклеотидные последовательности генов LMP из образцов предраковой (NORLMP и опухолевой (NPCLMP тканей и соответственно аминокислотные последовательности кодируемых ими белков. Гены NORLMP и NPCLMP встраивали в клетки ВЭБ-отрицательной линии TW01 и исслеовали иологические свойства трансфецированных клеток, в частности их способность к инвазивному росту in, устойчивость к апоптозу и экспрессии Е-кадгерина (CDH1). Результаты: оба белка — NORLMP1 и NPCLMP1 — значительно отличались по аминокислотной послеовательности от елка LMP1 дикого типа (B95,8), и клетки линии TW01, в которых они кспрессировались, различались по иологическим свойствам. Клетки TW01, экспрессирующие NORLMP1, обладали более злокачественным фенотипом, чем таковые, экспрессирующие NPCLMP1, по показателям инвазивной спосоности, устойчивости к апоптозу и регуляции кспрессии CDH1. Выводы: полученные данные свидетельствуют о том, что гены LMP , выделенные из образцов биопсии двух больных с различными стадиями РНГ, отличаются по нуклеотидной последовательности, что проявляется в различиях биологических свойств клеток, трансфецированных соотвествующими генами.